Investigation of Hyperconjugation Effect on Chemical Reactions and Compounds Stability - Nazimi, Gulnazir (Journal of Natural Sciences – Kabul University, 2021)
Allah created human beings with different perspectives (perception, understanding, behavior, ability, and influence in society), and no two individuals are identical in all qualities. Some people perceive everything negatively, while others view it positively. These collective properties of human beings affect society in multiple ways. In chemistry, there are also numerous electronic effects that influence chemical interactions, stabilizing the products and making the interacting compounds more or less reactive. These electronic effects make chemical interactions easier or harder. They also affect product yields, bond lengths, dipole moments, and the stability of alkenes, carbocations, acidity, and strength. The main electronic effects are the mesomeric effect, inductive effect, steric effect, and hyperconjugation effect. This work focuses on the hyperconjugation effect.